Effects of Low Doses of Glyphosate on Agronomic Traits of Upland Rice - Ferrari, Samuel [UNESP]; Marsala, Leonardo [UNESP]; Luís Oliveira Cunha, Matheus [UNESP] (Springer Nature, 2021)
Research has shown the occurrence of the hormesis effect in some upland rice cultures resulting from low-dose application of glyphosate. Glyphosate herbicide is widely used in Brazilian agriculture for controlling the large quantity of weeds. The aim of this work was to verify the effects of low-dose application of glyphosate herbicide on agronomic characteristics in upland rice. The experimental design used was randomized blocks comprising five low-dose applications of glyphosate herbicide (10, 20, 40, 70, and 100 g acid equivalent [a.e.] ha−1) and the control, in two stages of development of the rice culture (tillering [V4] and floral differentiation [R1]) with four repetitions. The agronomic traits of upland rice were evaluated. Data were subjected to variance analysis, polynomial regression analysis for the quantitative factor, and Tukey’s test for the qualitative factor at p < 0.05. The grain yield and the number of spikelets per panicle increased with the application of 10 g a.e. ha−1 of glyphosate at the floral differentiation stage. Until the low dose of 75 g a.e. ha−1, there was an increase in the number of panicles. Low doses between 70 and 100 g a.e. ha−1 applied in R1 provided less spikelets per panicle, lower 100-grain weight, and lower grain yield. The leaf flavonoid content increased due to the increase in the low doses of glyphosate herbicide.
Keywords: Glyphosate; Herbicide; Hormesis; Panicle; Yield